Can deterrence persist?: long-term evidence from a randomized experiment in street lighting - Mitre-Becerril, David (Criminology & public policy, 2022)
Research summary For centuries and even millenia, street lighting has been among the most ubiquitous capital investments that societies have made in public safety. Recent research by Chalfin et al. (2021) - the first randomized experiment that studies the effect of street lighting on public safety - demonstrated that a tactical street lighting intervention in New York City's public housing developments led to a 36% reduction in serious criminal activity during nighttime hours in the 6 months after the new lights were rolled out. But do the effects endure? In this study, we examine the longer-term effects of the same street lighting intervention using 3 years of outcome data. We show that the effects of the lighting intervention persist over time. Critically, the intervention reduced crime without eventually leading to a larger number of arrests. Policy implications As street lighting requires a large up-front capital investment, the attractiveness of enhanced lighting to policy makers depends critically on whether its public safety benefits will be long lasting. These findings provide some assurance that the impact of street lighting can endure beyond their initial installation. Because the lighting intervention reduced crime without increasing the number of arrests, it did not reduce crime by widening the net of the criminal justice system.